Economic culture and economic performance - Edmund S. Phelps (EconPol Forum, 2024)
This paper explores the effects of several cultural values, attitudes, and the like, on some of the main dimensions of economic performance. It shows a weak correlation between continental countries' relative endowment of some cultural attributes and the relative performance of their national economies. However, not all of the cultural attributes hypothesized to be important were found to matter for performance. And not all continental countries were under-endowed in some of the cultural attributes that mattered a lot.
Keywords: 330